2019
DOI: 10.1093/jmammal/gyz069
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive den selection and its consequences for fisher neonates, a cavity-obligate mustelid

Abstract: Selection of habitat characteristics by reproductive females during neonate development can mediate the influence of adverse environmental conditions on the fitness of offspring. Previous research has suggested that cavities and burrows used for reproduction by cavity-obligate species offer thermoregulatory benefits, access to prey, and can limit predation pressure. As fishers (Pekania pennanti) are secondary cavity-obligate breeders, we hypothesized that they select particular characteristics of reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Resource use of the similar-sized fisher has been reasonably wellstudied. Fishers tend to select home ranges and resting sites in areas of complex forest structure that provide sufficient prey, escape cover, and suitable microstructures for reproduction and resting (Green et al, 2019;Matthews et al, 2019;Zielinski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Resource use of the similar-sized fisher has been reasonably wellstudied. Fishers tend to select home ranges and resting sites in areas of complex forest structure that provide sufficient prey, escape cover, and suitable microstructures for reproduction and resting (Green et al, 2019;Matthews et al, 2019;Zielinski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Fishers are forest-dwelling meso-carnivores whose range in North America and the western states has substantially declined [ 29 , 30 ]. Fishers are associated with older forest elements such as large live trees, snags, and logs (e.g., [ 31 ]) and are a cavity denning obligate, thus they seek structures with specific shelter-providing cavities for parturition and kit development [ 32 ]. Fishers rest in similar structures throughout the year [ 23 , 33 ], and resting locations have been used to monitor habitat availability and trends [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, some species such as the fisher change den sites as their young develop enabling changes in den quality to be compared. Matthews et al, (2019) found that natal cavities where parturition occurred had significantly smaller openings than late maternal dens or non-maternal dens, and linked this to predation and Figure 4 The percentage of individuals (n) captured in a year (February-July) on each plot. Large cavities were provisioned on both plots in year 2 but only on plot 1 in year 1 and only on plot 2 in year 3. male harassment.…”
Section: Hypotheses To Explain the Need For A Maternal Cavitymentioning
confidence: 99%